2012
DOI: 10.1152/ajprenal.00531.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glomerulotubular balance. I. Impact of dopamine on flow-dependent transport

Abstract: .-In response to volume expansion, locally generated dopamine decreases proximal tubule reabsorption by reducing both Na/H-exchanger 3 (NHE3) and Na-K-ATPase activity. We have previously demonstrated that mouse proximal tubules in vitro respond to changes in luminal flow with proportional changes in Na ϩ and HCO 3 Ϫ reabsorption and have suggested that this observation underlies glomerulotubular balance. In the present work, we investigate the impact of dopamine on the sensitivity of reabsorptive fluxes to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…It has been demonstrated that the AT1 receptor is important to maximize the NHE3 activity activated by flow; however, it is not critical for the flow-stimulated HCO 3 − transport, which still exists when the inhibitors are present or when the AT1a receptor is knocked out [15]. Dopamine, which stimulates NHE3 endocytosis via a PKA-dependent mechanism, has no effect on baseline fluxes but abrogates the flow-stimulated Na + and HCO 3 − absorption [18]. A comparison of the changes in torque and changes in transport activity by flow showed that dopamine reduced, and blocking of the dopamine receptor increased the tubule sensitivity to microvillus torque.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the AT1 receptor is important to maximize the NHE3 activity activated by flow; however, it is not critical for the flow-stimulated HCO 3 − transport, which still exists when the inhibitors are present or when the AT1a receptor is knocked out [15]. Dopamine, which stimulates NHE3 endocytosis via a PKA-dependent mechanism, has no effect on baseline fluxes but abrogates the flow-stimulated Na + and HCO 3 − absorption [18]. A comparison of the changes in torque and changes in transport activity by flow showed that dopamine reduced, and blocking of the dopamine receptor increased the tubule sensitivity to microvillus torque.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies we have demonstrated that dopamine completely blocks flowstimulated Na ϩ transport and partially abolishes flow-stimulated HCO 3 Ϫ absorption, and the remaining portion of the increment of HCO 3 Ϫ reabsorption (J HCO3 ) by flow is blocked by the H-ATPase inhibitor bafilomycin. The effects of dopamine were completely abolished by the dopamine DA1 receptor antagonist Sch 23390 (5). We also demonstrated a dopamine-dependent decrease in the sensitivity of the renal brush border to a change in microvillous torque; a DA1 antagonist increased the transport sensitivity to torque.…”
mentioning
confidence: 58%
“…Additional studies of mouse tubules in vitro have demonstrated that it is possible for hormonal or autocrine signals to effect either or both baseline transport rates and flow sensitivity. For example, with the application of dopamine, baseline Na ϩ and HCO 3 Ϫ fluxes and the flow sensitivity of each were all reduced by dopamine (5). When the tubules were treated with both dopamine and a DA1 receptor blocker, there were modest increases in baseline flows, but dramatic increases in flow sensitivity for Na ϩ and HCO 3 Ϫ (2.5 and 3.5, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Costimulation of D 1 -and D 2 -like dopamine receptors results in synergism between these receptors to promote diuresis and natriuresis in rats (44). As previously indicated, D 1 -like dopamine receptors and ␣-ARs have opposing effects on Na ϩ transport (4,17,20,73). In the absence of D 1 -like dopamine receptors, the inhibitory effect of D 1 -like receptors on Na ϩ transport is diminished (1), whereas the ␣ 1A -AR predominates (present study).…”
Section: -Like Dopamine Receptor Interactions With and Regulationmentioning
confidence: 86%